Si junior... Exploring the issues inn having a gay child Parents' perspective. - Albasin, Ira Gem G., et al.; Caguicla, Maridel S.; Mesa, Arn Christian G. (Tacloban City Ira Gem G. Albasin, 2010)
This study was a challenge to begin in exploring the issues in having a gay son, specifically from the parents' perspective. Purposely, it focused on the views of parents about homosexuality, factors that facilitated the discovery of parents about their gay son, as well as their reaction, the kind of parent-child relationship they have with their gay sons and the quality at which this is sustained, the social issues surrounding the nature of being the parent of a homosexual male, the coping strategies that parents employ in dealing with the issues they are facing, and the acceptance process that parents experience in dealing with their son's sexuality. Participants were ten (10) parents of gays who were interviewed individually. Parents' view on homosexuality is influenced by their past experiences. Parents considered genetics as a primary cause as to their son's sexuality. All parents are disappointed and expressed apparent helpless disregard in the situation after realizing and confirming that their son is gay. Notably, most of the mothers treated the situation with a more enduring understanding and with a lightened manner compared to the fathers. The responses of parents about their current relationship with their sons were somehow overwhelmingly positive.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: Social Science